Longitudinal analysis of CYFRA 21-1 levels in patients with pulmonary nodules: Differential trajectories between benign and malignant cases - Yency J. Forero; Michael N. Kammer; Kevin C. McGann; Hudson Holmes; Sheau-Chiann Chen; Heidi Chen; Samson Argaw; Timothy A. Khalil; Sanja L. Antic; Yong Zou; Lianrui Zuo; Thomas A. Lasko; et al. (PLoS ONE, 2026)
Background CYFRA 21−1, a cytokeratin-19 fragment, is a validated serum biomarker for non-small cell lung cancer (NSCLC). However, most studies rely on single time-point measurements, limiting its specificity in differentiating malignancy from benign pulmonary conditions. Inspired by the clinical utility of serial PSA measurements in prostate cancer, we investigated whether longitudinal trends in CYFRA 21−1 could enhance diagnostic and monitoring capabilities in patients with pulmonary nodules. Methods and Findings We analyzed 132 patients with pulmonary nodules from the Vanderbilt Thoracic Biorepository. For the primary analysis, patients who underwent treatment prior to biomarker assessment were excluded, resulting in an untreated cohort of 121 patients (91 benign and 30 malignant nodules). CYFRA 21−1 levels were measured serially using electrochemiluminescence assays. Longitudinal trends were assessed using linear mixed-effects models to estimate biomarker trajectories. Primary analyses compared benign vs. malignant nodules using longitudinal modeling of log-transformed CYFRA 21−1 values. At baseline, CYFRA 21−1 levels were significantly higher in malignant versus benign nodules. Longitudinal mixed-effects modeling did not demonstrate statistically significant differences in trajectories between benign and malignant nodules. Benign nodules showed a small positive trend in log(CYFRA 21−1) whereas malignant nodules showed greater longitudinal variability. The magnitude of change assessed using the absolute slope of log(CYFRA 21−1) was significantly greater in malignant nodules compared with benign nodules (p < 0.05). Exploratory diagnostic analysis showed that baseline log(CYFRA 21−1) achieved and AUC of 0.68 (95% CI 0.56-0.79) with sensitivity 0.63 and specificity 0.71. The absolute slope of log(CYFRA 21−1) yielded an AUC of 0.67 (95% CI 0.48-0.87) with sensitivity 0.39 and specificity 0.97. Conclusions CYFRA 21−1 exhibits substantial within-patient variability over time, with trajectories that reflect disease state and treatment. These findings suggest that longitudinal monitoring of CYFRA 21−1 may provide additional information beyond single time-point measurements in the evaluation of pulmonary nodules. Further studies in large prospective cohorts are warranted to validate these findings before clinical implementation.